Improved storage area network method for backup approach - Sarmad K. Ibrahim; Saif A. Abdulhussien (Institute of Advanced Engineering and Science, 2020)
Storage Area Network (SAN) could be a dedicated storage network which carries the info between servers and storage devices. SAN offers flexibility to implement and share data between servers and remote devices instead of the traditional method that reduced the performance of service. This paper improves SAN backup method to increase the CPU utilization and reduce the load on the link; the result shows that the improved method is better than of traditional in terms of response time in FTP about 36% while the traffic data is about 3%.